2011
DOI: 10.3389/fnbeh.2011.00077
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Fear-Potentiated Startle Paradigms for Assessing Human Conditioned Fear Extinction and Return of Fear

Abstract: Fear conditioning methodologies have often been employed as testable models for assessing learned fear responses in individuals with anxiety disorders such as post-traumatic stress disorder (PTSD) and specific phobia. One frequently used paradigm is measurement of the acoustic startle reflex under conditions that mimic anxiogenic and fear-related conditions. For example, fear-potentiated startle is the relative increase in the frequency or magnitude of the acoustic startle reflex in the presence of a previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
(47 reference statements)
1
30
1
Order By: Relevance
“…Traditionally, these data provide the experimenter with validation that the CS–US association was successfully learned during fear acquisition in that there is often a high correlation between physiological indices of fear (e.g., startle, skin conductance) and US-expectancy responses (e.g., Norrholm, Anderson, et al, 2011; Norrholm, Jovanovic, et al, 2011). As the study of conditioned fear is extended into fear extinction and return of fear paradigms (which often include multiple test sessions with varying temporal and contextual factors), dissociations begins to emerge between physiological measures and US-expectancy responses (see (Kindt & Soeter, 2013; Norrholm et al, 2008; Soeter & Kindt, 2010, 2011b; Weike et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, these data provide the experimenter with validation that the CS–US association was successfully learned during fear acquisition in that there is often a high correlation between physiological indices of fear (e.g., startle, skin conductance) and US-expectancy responses (e.g., Norrholm, Anderson, et al, 2011; Norrholm, Jovanovic, et al, 2011). As the study of conditioned fear is extended into fear extinction and return of fear paradigms (which often include multiple test sessions with varying temporal and contextual factors), dissociations begins to emerge between physiological measures and US-expectancy responses (see (Kindt & Soeter, 2013; Norrholm et al, 2008; Soeter & Kindt, 2010, 2011b; Weike et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The eyeblink component of the acoustic startle response was measured according to previously published methods (Norrholm et al, 2006; Norrholm, Anderson, et al, 2011; Norrholm, Jovanovic, et al, 2011). The startle probe was a 108-dB [A], 40 ms burst of white noise with near instantaneous rise time delivered binaurally with headphones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, startle entails postural (see above), autonomic (e.g., Hamm et al 2003a), and electrocortical (e.g., Schupp et al 1997) responses serving to make the subject ready for an imminent fight-or-flight situation, as well as modulations of the postauricular reflex (e.g., Benning et al 2004;Franklin et al 2013a) (note that the latter can reveal positive valence by increased amplitude). In humans, as in rats, the amplitude of the startle response is increased in the presence of a shock-associated or an aversive stimulus (Lang et al 1990;Grillon and Baas 2003;Andreatta et al 2010;Norrholm et al 2011). In turn and important in the current context, numerous studies have revealed that startle is decreased by stimuli associated with reward or pleasure (e.g., Geier et al 2000;Skolnick and Davidson 2002;Conzelmann et al 2009), although there is a lack of pure reward-conditioning studies with the startle response as a dependent measure.…”
Section: Humans Punishment-and Reward-learningmentioning
confidence: 99%
“…In order to bridge this gap, Norrholm and colleagues examined the use of auditory and visual CSs in fear conditioning of healthy participants (58). Briefly, healthy participants acquired fear to auditory stimuli comparable to the participants who were fear conditioned with visual stimuli.…”
Section: Versatilitymentioning
confidence: 99%